GAMIFICATION BASED ON LOCAL STORIES’ EFFECT ON STUDENTS’ LEARNING MOTIVATION - Sari, Komang Bela Pradnya; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2020)
In the 21st century, the use of innovative and digital-based teaching media are required. This research aimed at examining the effect of gamification based on local stories as teaching media on fifth grade elementary school students’ motivation. Quasi experimental with one group pre-test post-test design was implemented. The study was conducted at SD N 1 Penarukan where 25 of fifth grade students in academic year 2019/2020 were involved as the sample of study. Three instruments were administered to collect the data; pre-test post-test, treatment instrument and interview. The result showed that post-test mean score has significantly improved compared to pre-test score (42.29 > 23.35). Hypothesis testing result (paired sample t-test) showed the tobs value was higher than tcv (20.811>1.677) with α = 0.05, which indicated that gamification positively affected students’ motivation. The interview result revealed that the students are highly motivated to learn by using gamification.